A Novel Homozygous Missense Variant in the LRRC32 Gene Is Associated With a New Syndrome of Cleft Palate, Progressive Vitreoretinopathy, Growth Retardation, and Developmental Delay - Zufit Hexner-Erlichman; Boris Fichtman; Yoav Zehavi; Yoav Zehavi; Morad Khayat; Haneen Jabaly-Habib; Haneen Jabaly-Habib; Lee S. Izhaki-Tavor; Moshe Dessau; Orly Elpeleg; Ronen Spiegel; Ronen Spiegel (Frontiers Media S.A., 2022)
Cleft lip and/or cleft palate are a common group of birth defects that further classify into syndromic and non-syndromic forms. The syndromic forms are usually accompanied by additional physical or cognitive abnormalities. Isolated cleft palate syndromes are less common; however, they are associated with a variety of congenital malformations and generally have an underlying genetic etiology. A single report in 2019 described a novel syndrome in three individuals, characterized by cleft palate, developmental delay and proliferative retinopathy due to a homozygous non-sense mutation in the LRRC32 gene encoding glycoprotein A repetitions predominant (GARP), a cell surface polypeptide crucial for the processing and maturation of transforming growth factor β (TGF-β). We describe a patient who presented with cleft palate, prenatal and postnatal severe growth retardation, global developmental delay, dysmorphic facial features and progressive vitreoretinopathy. Whole exome sequencing (WES) revealed a very rare homozygous missense variant in the LRRC32 gene, which resulted in substitution of a highly conserved isoleucine to threonine. Protein modeling suggested this variant may negatively affect GARP function on latent TGF-β activation. In summary, our report further expands the clinical features of cleft palate, proliferative retinopathy and developmental delay syndrome and emphasizes the association of LRRC32 pathogenic variants with this new syndrome.